Suitable Reference Genes for Accurate Gene Expression Analysis in Parsley (Petroselinum crispum) for Abiotic Stresses and Hormone Stimuli - Li, Meng-Yao; Song, Xiong; Wang, Feng; Xiong, Ai-Sheng (Frontiers in Plant Science, 2016)
Parsley is one of the most important vegetable in Apiaceae family and widely used in food industry, medicinal and cosmetic. The recent studies in parsley are mainly focus on chemical composition, further research involving the analysis of the gene functions and expressions will be required. qPCR is a powerful method for detecting very low quantities of target transcript levels and widely used for gene expression studies. To ensure the accuracy of results, a suitable reference gene is necessary for expression normalization. In this study, three software geNorm, NormFinder, and BestKeeper were used to evaluate the expression stabilities of eight candidate reference genes (GAPDH, ACTIN, eIF-4α, SAND, UBC, TIP41, EF-1α, and TUB ) under various conditions including abiotic stresses (heat, cold, salt, and drought) and hormone stimuli treatments (GA, SA, MeJA, and ABA). The results showed that EF-1α and TUB were identified as the most stable genes for abiotic stresses, while EF-1α, GAPDH, and TUB were the top three choices for hormone stimuli treatments. Moreover, EF-1α and TUB were the most stable reference genes across all the tested samples, while UBC was the least stable one. The expression analysis of PcDREB1 and PcDREB2 further verified that the selected stable reference genes were suitable for gene expression normalization. This study provides a guideline for selection the suitable reference genes in gene expression in parsley.